FERMENTATION USING SCOBY TO IMPROVE THE SENSORY CHARACTERISTICS AND ANTIOXIDANT ACTIVITY OF CHAYOTE (Sechium edule) JUICE - Julia Ratna Wijaya; Angel Athalia (Jurnal Sains dan Teknologi Pangan, 2023)
Chayote (Sechium edule) is known to be rich in antioxidants. Its use in food products, however, is still limited. It is likely due to its greeny flavour. To increase its consumption, the use of chayote in food product development that can reduce or eliminate its greeny flavour is required. Fermentation is one of the common methods that can improve the sensory and functional properties of foodstuffs. This study was aimed to use SCOBY fermentation to improve the sensory characteristics and antioxidant activity of chayote juice. Three level of sugar concentration and 4 level of fermentation times were used as the variables. The result showed that increasing the sugar concentration significantly increased the total dissolved solids, but decreased the total acid, thus increased the pH of the fermented chayote juice. Prolonging the fermentation time significantly increased the total acids, decreased the pH and the total dissolved solids. SCOBY fermentation applied on the chayote juice significantly increased the sensory acceptance level as well as the antioxidant activity at least 3 times but could be up to 7.7 times. Chayote fermented beverage with the sugar concentration of 35% fermented using SCOBY for 6 days had the highest overall preference with the level of acceptance as “like”: Its antioxidant activity was 287.805 ± 13.74 mgAA/L which was 6.8 times higher than the juice. It had total phenolic of 185.96 ± 2.81 mgGA/L, and total flavonoids of 10.36 ± 1.22 mgQE/L.